On k-Jacobsthal and k-Jacobsthal-Lucas hybrid numbers - Kilic, Nayil (Journal of discrete mathematical sciences & cryptography, 2021)
In this paper, we consider the k-Jacobsthal and k-Jacobsthal-Lucas hybrid numbers. We obtain the Binet formulas, generating functions, exponential generating functions and summation formulas of k-Jacobsthal and k-Jacobsthal-Lucas hybrid numbers. Also, we give Catalan, Cassini and d'Ocagne identities of these hybrid numbers. Finally, we introduce the matrix generators for k-Jacobsthal and k-Jacobsthal-Lucas hybrid numbers.